In vitro Regeneration of an Endangered Medicinal Orchid Dendrobium crepidatum Lindl. & Paxton through Protocorm like bodies. (Plant Tissue Culture and Biotechnology, 2023)
A protocol for regeneration of an endangered medicinal orchid Dendrobium crepidatum was established mainly via indirect protocorm like body (PLBs) formation. The PLBs procured from in vitro growth cultures was assessed in ½ MS medium alone and in combinations with 6-Benzyl amino purine (BAP), Kinetin (Kn) and α-Naphthalene acetic acid (NAA). The calli were induced from longitudinally bisected segments of PLBs. The optimum percentage of callus was obtained in ½ MS medium supplemented with BAP (1.0 mg/l) and combination of BAP (1.0 mg/l) with NAA (0.5 mg/l), where 64.3% and 83.3% of callus was formed respectively. PLB formation was achieved when callus was transferred onto the respective combinations in ½ MS basal medium. The optimum percentage (91.6%) of PLBs were regenerated in the combination of BAP with NAA. These PLBs differentiated into intact plantlets about 3 cm in height and with 4-5 roots were transplanted into potting mixture with highest rate of 93.3% survival rate in a green house.